On Being a Homeless Work of Fiction: Narrative Quests and Questions. Issue 1 (May 2016) - Herrmann, Andrew F.
In this piece the author takes a journey into the meaning of quests through the philosophical terrain of existential phenomenology and authenticity. Unlike quest narratives in literature and popular culture, our life narratives are not yet finished, but ongoing. Comparing the idea of existential homelessness with its undeniable and constant change to that of autoethnographic writing, he examines narrative and memory and how current life events change our understandings of past narratives and our sense of identity. Our life narratives are made up of fragmented thoughts and ideas, the stories others told before we were born—and will tell about us after we are gone.